QUALITATIVE EXAMINATION OF ANTHROPOMETRICAL PARAMETERS IN PRESCHOOL CHILDREN - Trpkovska, Biljana; Zafirova, Biljana; Papazova, Marija; Zhivadinovikj, Julija; Bojadzieva, Biljana; Chadikovska, Elizabeta; Dodevski, Ace (EUROPEAN ASSOCIATION OF CLINICAL ANATOMY (EACA), 2019)
Introduction Growth monitoring and promotion of optional growth are essential components of primary health care for children.The aim of this research is to present qualitative examination of anthropometrical parameters in preschool children and provide the information on the prevalence of different categories of growth and nutritional status during the childhood. Matherial and methods The study included 220 healthy preschool children (110 boys and 110 girls). Stature and body weight were measured, and the BMI value was calculated. Ten anthropometric parameters were measured such as body weight, body height, longitudinal and transversal diameters and skin folds for triceps and scapula. We used self-organizing maps for additional qualitative examination of the results. Results Values at the 50th percentile in our children from both nationalities for the weight-for-age index were 20 kg. The height-for-age index values corresponding to the 50th percentile showed slightly higher values in our female subjects 115.0 cm, and those in our male subjects was 110 cm. The values of 50th percentile of BMI in our females subjects was 15.7 kg/m², whereas in our males was 16.1 kg/m². The values of 50th percentile of BMI in our females subjects from muslims nationalities was 16.2 kg/m², whereas in males was 16.68 kg/m². Conclusion These results show that obesity prevention is recommended, and the detected values could be applied for evaluation of deviations in growth and nutritional status in preschool children.
Abstract book, 2019, Madrid, (ISCAA)
Keywords: anthropometry; preschool children; growth